Does digital literacy foster disbelief in fake news? Efficacy of attitudes and strategies against disinformation in Mexico - Echeverría, Martín (2023)
If successful, disinformation operations on social media could generate false beliefs in the public and lead them to take political decisions contrary to their interests. In response to this, various actors have implemented measures, among which stand out the (self) regulation of algorithms to signal malicious information and informational literacy actions. Nevertheless, there is still not enough empirical evidence to account for the extent to which false information generates false beliefs, as well as the efficacy of the aforementioned actions to reduce citizen credulity. This study uses a representative survey applied during the 2021 elections in Mexico (n = 1750) that predicts the extent to which the use of social networks to follow the campaign has an effect on credulity in false information. At the same time, we observe how these effects are moderated on the one hand by the different platforms, whose architecture is more or less prone to alerting about disinformation, and on the other, by citizens' attitudes and strategies to prevent being misinformed. We find that the use of platforms that have used measures to alert about disinformation does not predict greater or lesser credulity, but instead WhatsApp, with fewer controls and a more private character, does increase it. On the other hand, the exercise of strategies does not reduce credulity in disinformation, unlike attitudes against it, which substantially decreases it.